Interactions between 4-thiothymidine and water-soluble cyclodextrins: Evidence for supramolecular structures in aqueous solutions - Rizzi, Vito; Matera, Sergio; Semeraro, Paola; Fini, Paola; Cosma, Pinalysa (Beilstein Journal of Organic Chemistry, 2016)
Since several years the inclusion of organic compounds (guests) within the hydrophobic cavity (host) of cyclodextrins (CDs) has been the subject of many investigations. Interestingly, the formation of inclusion complexes could affect the properties of the guest molecules and, for example, the influence of the delivery system can be a method to improve/change the photochemical behavior of the guest. In particular, very recent studies have shown the protective role of CDs preventing the degradation of the encapsulated guest. Starting from this consideration, in this work, only the structure and complexation mode of the inclusion complexes involving 4-thiothymidine (S4TdR, a known photosensitizer) and five CDs, namely 2-hydroxypropyl-α-cyclodextrin (2-HP-α-CD), 2-hydroxypropyl-β-cyclodextrin (2-HP-β-CD), 2-hydroxypropyl-γ-cyclodextrin (2-HP-γ-CD), heptakis-(2,6-di-O-methyl)-β-cyclodextrin (DIMEB CD) and heptakis-(2,3,6-tri-O-methyl)-β-cyclodextrin (TRIMEB CD) were investigated by different spectroscopic techniques (UV–vis, FTIR–ATR, 1H NMR) and cyclic voltammetry analysis (CV). This work is necessary for a prospective research on the photoreactivity of S4TdR in aqueous environment and in the presence of CDs to prevent its degradation under irradiation. UV–vis, FTIR–ATR and CV measurements suggested the formation of supramolecular structures involving the employed CDs and mainly the pyrimidine ring of S4TdR. 1H NMR analyses confirmed such indication, unveiling the presence of inclusion complexes. The strongest and deepest interactions were suggested when TRIMEB and DIMEB CDs were studied. The S4TdR affinity towards CDs was also evaluated by using the Benesi–Hildebrand (B–H) equation at 25 °C employing CV and 1H NMR methods. The stoichiometry of the interaction was also inferred and it appears to be 1:1 for all examined CDs.
Keywords: cyclodextrins; inclusion complex; photodynamic therapy